Recommendations to meet statistical challenges arising from endpoints beyond overall survival in clinical trials on chronic myeloid leukemia - Pfirrmann, Markus; Hochhaus, Andreas; Lauseker, Michael; Saußele, Susanne; Hehlmann, Rüdiger; Hasford, Joerg (Leukemia, 2011)
The aim of this work was to provide guidelines for appropriate statistical analyses regarding most common endpoints in clinical trials on chronic myeloid leukemia: hematologic, cytogenetic and molecular results, failure-free and event-free survival, and progression-free and overall survival. The reasons for the specified recommendations are explained and important issues are outlined by comprehensive examples. Particular attention is paid to the warning of the application of suboptimal methods that may lead to seriously biased results and conclusions. In the presence of a competing risk like death, Kaplan-Meier analysis should not be applied for time-to-remission endpoints. The appropriate method to estimate the probabilities of a time-to-remission endpoint is the calculation of its cumulative incidence function. However, the exact date of remission is hardly known. Detection of remission depends strongly on evaluation frequencies. Complex composite endpoints comprising many events with considerably heterogeneous severity imply difficulties with interpretation. Time-to-remission and complex composite endpoints are not recommended for primary judgment on efficacy. It is rather advisable to investigate remission status at a fixed time point as a primary endpoint, followed by progression-free and overall survival. For patients with the intended remission success at the time point of interest, relapse-free survival provides an additional primary outcome.
Gesehen am 12.12.2022